2014
DOI: 10.1111/jir.12143
|View full text |Cite
|
Sign up to set email alerts
|

Social networks of people with mild intellectual disabilities: characteristics, satisfaction, wishes and quality of life

Abstract: The significance of family and the importance of high-quality interpersonal relationships between professional and client in the lives of young adults with ID cannot be overestimated. Although measures of satisfaction and wishes can have limitations, in actual practice it is considered useful to assess the opinions of clients with respect to their social networks. Interventions can then be tailored to the needs and wishes of the persons themselves.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
53
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(62 citation statements)
references
References 39 publications
8
53
1
Order By: Relevance
“…For example, one of the indicators of the quality of interpersonal relations is the social network of the person. This finding is supported by social network's literature where two perspectives emerge to understand and measure the concept (Forrester‐Jones et al, ; Lunsky, ): a structural one (e.g., in terms of size and frequency) and a functional one (e.g., in terms of perceived emotional and practical support) (Van Asselt‐Goverts, Embregts, & Hendriks, ).…”
Section: Discussionsupporting
confidence: 54%
“…For example, one of the indicators of the quality of interpersonal relations is the social network of the person. This finding is supported by social network's literature where two perspectives emerge to understand and measure the concept (Forrester‐Jones et al, ; Lunsky, ): a structural one (e.g., in terms of size and frequency) and a functional one (e.g., in terms of perceived emotional and practical support) (Van Asselt‐Goverts, Embregts, & Hendriks, ).…”
Section: Discussionsupporting
confidence: 54%
“…A supported social network is critical to the feeling and experience of social inclusion (Van Asselt‐Goverts et al . ). In addition to the forming of interpersonal relationships, the social group also fostered physical activity and community participation.…”
Section: Discussionmentioning
confidence: 97%
“…Van Asselt‐Goverts et al . ) and greater involvement of family increased community participation (e.g. Amado et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It can also be argued that having children or partner per se does not have an impact on loneliness but it is the nature of relationships with these family members that is important. For instance, Asselt‐Goverts, Embregts, and Hendriks () found that one of the most valued elements of a relationship with family members in people with DD is affection. Thus, the exploration of the nature of relationships with close network members could have yielded significant results.…”
Section: Discussionmentioning
confidence: 99%